The Impact of After-sales Service Quality on Customer Satisfaction and Customer Loyalty of Middle-upper Class Landed Housings - Didik Wahjudi; Timoticin Kwanda; Rianthi Sulis (Jurnal Teknik Industri, 2018)
Nowadays, good products are not sufficient. Market competition requires a good after-sales service. After-sales service quality has been identified as a source of revenue and competitive advantage. While other industry sectors have readily paid attention to after-sales service quality, little study has been done on the effectiveness of after-sales service quality in the field of real estate. This study aims to explore the relationship among after-sales service quality, customer satisfaction, and customer loyalty. Especially, we want to confirm the impact of after-sales service quality on customer satisfaction and customer loyalty of middle-upper class real estate in Surabaya. This research was conducted by survey on 170 respondents from four housing complexes in Surabaya, i.e. Pakuwon City, Citraland, Bukit Darmo Golf, and Graha Family. The data was examined by using structural equation modeling (SEM). Through data analysis we confirm the positive correlation between after-sales service quality and customer satisfaction, the positive correlation between customer satisfaction and customer loyalty, and the direct and indirect relationships between after-sales service quality and customer loyalty. The practical implication of this study provides assurance to real estate management on the effectiveness of after-sales service quality in maintaining old customers and encouraging new consumers.